THE CONTRIBUTION OF HABLUMMINANNAS TO THE DEVELOPMENT OF PSYCHOLOGICAL WELL-BEING - Iskandar, Willem; Hidayat, Bahril (Psikis : Jurnal Psikologi Islami, 2023)
Social interaction in Islam is also referred to as "hablumminannas." Social interaction is an integral part of fulfilling the commandments of Allah SWT. The interpersonal dimension plays a crucial role in this principle. This study aims to explore the contribution of hablumminannas to psychological well-being by analyzing existing literature. The research employs a literature review as the research method. The author finds that the positive relationship aspect within hablumminannas has a significant impact on the development of individuals psychological well-being. Hablumminannas contributes in a way that affects psychological well-being. By fostering good relationships with others, prioritizing concern for others, and practicing effective communication and conflict resolution, the practice of hablumminannas can have a positive impact on individual psychological well-being.